Kin selection: fact and fiction - Griffin, A; West, SA (2002)
Hamilton's inclusive fitness theory represents one of the most important developments in evolutionary biology. In particular, the idea that individuals benefit from the reproduction of relatives (kin selection) has been extraordinarily successful in explaining a wide range of phenomena, especially cases of supposed altruism. However, recent work has emphasized how the importance of kin selection can be overestimated -an estimate of high relatedness between interacting individuals is not in itself sufficient evidence that kin selection is responsible for promoting altruism. In particular, supposedly altruistic traits can have direct fitness benefits, and competition between relatives can reduce the importance of indirect fitness benefits.